1995
DOI: 10.1111/j.1600-0447.1995.tb09595.x
|View full text |Cite
|
Sign up to set email alerts
|

Attempted suicide predicts suicide risk in mood disorders

Abstract: Suicide risk was studied in a sample of 346 mood disorder inpatients, 92 of whom were admitted after a current suicide attempt. The overall suicide mortality after a mean observation period of 6 years was 8%. The potential of attempted suicide to predict suicide risk in hospitalized patients with mood disorders was studied by survival analysis after subgrouping on the basis of whether a current suicide attempt had occurred or not. The suicide risk the first year after attempting suicide was 12% (11/92), compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
3
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 20 publications
7
65
3
2
Order By: Relevance
“…reported completed suicide rates of 15% for recent suicide attempters and 5% for non-attempters in patients with mood disorders. 43 Studies of completed suicides have shown that more than 50% of suicide completers had a previous attempt. 37,44 Tsai et al conducted a chart review in a sample of 125 bipolar patients who died from suicide and found that 51.2% of them had previous attempts, especially in the first seven years of disease (at least 1 suicide attempt in the previous seven years before the completion).…”
Section: Suicide Attempts and Bipolar Disordermentioning
confidence: 99%
“…reported completed suicide rates of 15% for recent suicide attempters and 5% for non-attempters in patients with mood disorders. 43 Studies of completed suicides have shown that more than 50% of suicide completers had a previous attempt. 37,44 Tsai et al conducted a chart review in a sample of 125 bipolar patients who died from suicide and found that 51.2% of them had previous attempts, especially in the first seven years of disease (at least 1 suicide attempt in the previous seven years before the completion).…”
Section: Suicide Attempts and Bipolar Disordermentioning
confidence: 99%
“…In several earlier studies, as risk factors for completed suicide in MDD have been identified to include among others: a history of previous suicide attempts (Fawcett et al, 1987, Nordström et al, 1995Angst et al, 2005;Coryell & Young, 2005), male sex (Modestin & Kopp, 1988;Höyer et al, 2004), previous psychiatric hospitalizations (Modestin & Kopp, 1988;Höyer et al, 2004;Coryell & Young, 2005), hopelessness (Fawcett et al, 1987;Coryell & Young, 2005), suicidal ideation (Fawcett et al, 1987;Coryell & Young, 2005), comorbid substance use disorder (Fawcett et al, 1987;Dumais et al 2005), comorbid personality disorder (especially Cluster B) (Hansen et al, 2003;Dumais et al 2005), anxiety (Fawcett et al, 1987) and increasing age (Höyer et al, 2004). (Table 2).…”
Section: Risk Factors For Completed Suicide In Mddmentioning
confidence: 99%
“…c Adjusted for age, gender, race, education, marital status, and rank. (Beck et al, 1999;Brown et al, 2000;Nordstrom et al, 1995). Therefore, past-year suicide ideation and attempts-as measured in this study-are an index of risk for future completed suicide as well as future suicide attempts.…”
Section: Comorbidity Of Ptsd and Depressionmentioning
confidence: 99%